Inovasi Digital Classifypro Cp untuk Efisiensi Klasifikasi Atlet Sepak Bola Cerebral Palsy di Tokyo - Kusdiana, Faris Rahman; Perdana, Suryo Saputra (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Cerebral Palsy (CP) is a permanent neurological condition affecting movement, muscle tone, and posture. This community service activity aimed to introduce ClassifyPro CP, a decision-support tool for the objective and efficient classification of CP Football athletes. The program was conducted in two sessions: an online Zoom Meeting (May 18, 2025) with 37 participants from Indonesia and Japan, and an offline presentation at Tokyo Metropolitan University (May 29, 2025) with 20 participants including physiotherapy students and lecturers. The activities included presentations, scientific counseling, interactive discussions, and application trials. The results showed participants’ enthusiasm, particularly regarding integration with IFCPF classification standards. This activity benefits participants by improving understanding of objective classification, encouraging student innovation, and opening opportunities for international research collaboration.